English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Factor.
Explain/show steps:
(x-y)²-3(y-x)³=

2007-07-05 18:47:47 · 7 answers · asked by Anonymous in Science & Mathematics Mathematics

7 answers

(y-x)^3=-(x-y)^3
(x-y)^2-3(y-x)^3=
(x-y)^2+3(x-y)^3=
[(x-y)^2][1+3(x-y)]

2007-07-05 18:52:57 · answer #1 · answered by Anonymous · 0 0

Each of the two terms can have (x - y)^2 factored out. That
makes the expression equal to:

[(x - y)^2]*[1 + 3(x - y)] = [(x - y)^2]*[3x - 3y + 1]


*Note that (y - x)^3 = [(-1)^3][(x - y)^3] = -(1)[(x - y)^2][x - y]

2007-07-05 19:11:50 · answer #2 · answered by TBone 1 · 0 0

= (x - y)² - 3.[- (x - y) ] ³
= (x - y)² + 3.(x - y)³
= (x - y)² [1 + 3 (x - y) ]

2007-07-09 11:01:58 · answer #3 · answered by Como 7 · 0 0

(x-y)²-3(y-x)³
=(y-x)^2- 3(y-x)^3 [(x-y)^2 = (y-x)^2]
=(y-x)^2[1-3(y-x)] {Factor out the (y-x)^2}

2007-07-05 19:16:45 · answer #4 · answered by ironduke8159 7 · 0 0

(x-y)²-3(y-x)³
=(x-y)²+3(x-y)³
Take (x-y)² common out of two terms
=(x-y)²[1+3(y-x)]
=(x-y)²(1-3x+3y)

2007-07-05 18:51:40 · answer #5 · answered by Jain 4 · 0 0

in case you meant to evalute it could be something like this: 4xy²(3y-x)-2x²(x-3y)² = 4x(y^3-xy^2)-2x^2(x^2-9y^2) = 4(xy^3-x^2y^2)-2(x^4-9x^2y^2) = 4xy^3-4x^2y^2-2x^4+18x^2y^2 = 14x^2y^2-2x^4+4x^3 answer: 14x^2y^2-2x^4+4x^3 (P.S. Sorry for the ^ sign cse i could no longer get it to alter into superscript....)

2016-10-19 02:35:37 · answer #6 · answered by ? 4 · 0 0

(x-y)²(1-3x+3y)

2007-07-05 20:58:15 · answer #7 · answered by lukey7650 2 · 0 0

fedest.com, questions and answers